Application of internet-based tools in integrated English language skills classes for open/online distance learning (ODL) / Siti Mariam Mohammad Iliyas ... [et al.] - Mohammad Iliyas, Siti Mariam; Taib, Siti Aishah; Noorezam, Maisarah; Sa'adan, Nadzrah (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
The application of various approaches is an integral part of a teaching and learning session. Numerous tools and techniques are readily available to be integrated into the sessions to ensure that the outcomes desired can be successfully achieved. However, thorough consideration and preparation must be done when it comes to choosing and integrating suitable tools. Some of the aspects considered are the learning outcomes, the types and function of the tools, and the usability of the chosen tools, which includes the materials and interaction tools. This paper presents the application of internet-based tools in integrated English language skills classes for open/online distance learning (ODL) which includes the pre, while, and post stages of the teaching and learning session.